2019
DOI: 10.3390/s19143211
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sapphire-Fiber-Bragg-Grating-Based Multi-Point Temperature Sensor in Boilers at a Commercial Power Plant

Abstract: Readily available temperature sensing in boilers is necessary to improve efficiencies, minimize downtime, and reduce toxic emissions for a power plant. The current techniques are typically deployed as a single-point measurement and are primarily used for detection and prevention of catastrophic events due to the harsh environment. In this work, a multi-point temperature sensor based on wavelength-multiplexed sapphire fiber Bragg gratings (SFBGs) were fabricated via the point-by-point method with a femtosecond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Deng et al [144] demonstrated an FBG sensing system with 14 optical fibres in total of 218 FBGs for winding temperature monitoring in a 35 kV/4000 kVA oil-immersed power transformer, and the hot-spot was accurately located in a temperature-rise test. Yang et al [145] fabricated multipoint temperature sensors based on sapphire FBGs and applied them in boilers at a commercial power plant for more than 40 days, the performance was consistent with measurement range between room temperature and 1200°C. However, the distance of distributed sensing for FBG-based fibre temperature sensors is limited by the number of FBGs because signal demodulation is hard to realise for too many FBGs with different λ B , and the peak shift is difficult to be determined if the temperature to be measured is not uniform.…”
Section: Fbg-based Optical Fibre Temperature Sensormentioning
confidence: 71%
See 2 more Smart Citations
“…Deng et al [144] demonstrated an FBG sensing system with 14 optical fibres in total of 218 FBGs for winding temperature monitoring in a 35 kV/4000 kVA oil-immersed power transformer, and the hot-spot was accurately located in a temperature-rise test. Yang et al [145] fabricated multipoint temperature sensors based on sapphire FBGs and applied them in boilers at a commercial power plant for more than 40 days, the performance was consistent with measurement range between room temperature and 1200°C. However, the distance of distributed sensing for FBG-based fibre temperature sensors is limited by the number of FBGs because signal demodulation is hard to realise for too many FBGs with different λ B , and the peak shift is difficult to be determined if the temperature to be measured is not uniform.…”
Section: Fbg-based Optical Fibre Temperature Sensormentioning
confidence: 71%
“…Deng et al [144] demonstrated an FBG sensing system with 14 optical fibres in total of 218 FBGs for winding temperature monitoring in a 35 kV/4000 kVA oil‐immersed power transformer, and the hot‐spot was accurately located in a temperature‐rise test. Yang et al [145] fabricated multipoint temperature sensors based on sapphire FBGs and applied them in boilers at a commercial power plant for more than 40 days, the performance was consistent with measurement range between room temperature and 1200°C.…”
Section: Review On Optical Fibre Sensors For Electrical Equipment Cmentioning
confidence: 72%
See 1 more Smart Citation
“…By the way of the Bragg grating written into silica with femtosecond lasers using either the phase mask method or the point-by-point method, fiber Bragg gratings (FBGs) could be used for sensing strain and/or temperature in environment at temperatures less than 1000 °C [ 10 ]. Consider the most widely used optical fiber material, fused silica, being incapable of withstanding the chemically corrosive environments, the sapphire-FBG based temperature sensor was fabricated and packaged to show great linearity of temperature response from room temperature to elevated temperature [ 11 ]. For structural health monitoring of the next-generation of nuclear reactors, different technologies for realizing temperature resistant FBGs were developed for temperature and strain measurements especially for components exposed to high temperature and radiation levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The performances of conventional room-temperature sensors, including sensitivities, response times, and lifetime, degrade rapidly when temperature gets lower. A few applications using optical fiber sensors at cryogenic temperatures have been developed lately, such as FBGs embedded in or bonded to substrates (e.g., PMMA, Teflon) with larger thermal expansion coefficients for overcoming their low temperature sensitivity, a continuous liquid level sensing system for liquid nitrogen and helium tanks [ 11 , 17 ].And some optical fiber sensors including FBG, Raman-scattering, Rayleigh-scattering and Brillouin-scattering for monitoring cryogenic temperature of high-temperature superconducting tapes at 77 K or even lower temperature have been attempted [ 20 , 21 , 22 , 23 ]. In these investigations, optical fiber sensors were mainly developed to measure cryogenic temperature in which the deformation of the materials and structures commonly were not considered.…”
Section: Introductionmentioning
confidence: 99%